Analysis of Code of Conduct Responsibilities Fisheries (CCRF) on Fishing Gear in Dumai - Tyas Dita Pramesthy; Ratu Sari Mardiah (Jurnal Perikanan dan Kelautan, 2019)
The development of capture fisheries based on the Code of Conduct for Responsible Fisheries (CCRF) use to optimally the potential of capture fisheries. Fishing gears that use in Dumai City are gill net, push net, and drifting longline. The research was conducted to analyze the fishing gear that used by fishermen in Dumai City based on the CCRF document as a continuation in providing policies of fishing gear. The method of data collection is use a questionnaire and statistic of description is used to data analysis. The results showed the drawbacks of the use of gill nets that are found in the quality of fish caught tend to be slightly physically defective (part of the operculum), and can make the to other species die because the net traps and makes fish spun. Sondong can not be recommended as a good fishing gear based on the CCRF, because the mesh size used is small so the selectivity of sondong is low, and the technique of sondong operation can damage the habitat. Drifting longline is a fishing gear that is selective and environmentally friendly, although viewed from the types of fish that caught, longline has the potential to catch the fish that protected by law based on the main catch is stingrays. However, stingrays that caught by fishermen in dumai are not the fish that protected by law. The conclusion of the study is gill net and drifting longline are recommended fishing gear to fishermen in Dumai city, because it is appropriate with the provisions of the CCRF document